PROBLEMS OF CREATING A MOBILE APPLICATION FOR A BIBLIOGRAPHIC INFORMATION SEARCH ENGINE - Karataev, Р.Қ; Baibaktina, А.Т (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
Currently, the number of resources available on the Internet is significantly increasing. It then has a large amount of information, but without mastering the content. In this vast data warehouse, the research of modern information search engines does not allow users to get results for their queries that exactly meet their needs. This is largely due to indexing methods (keywords, thesaurus). The result is that the network user spends most of their time exploring a large number of web pages, looking for what they need, because the network does not provide services in this direction. The article presents the technology of creating a bibliographic information search system.We also consider the issues of choosing the environment for creating an information search system and establishing advanced information search modes (standard, advanced, professional, dictionary, etc.).